2018
DOI: 10.1021/acs.jpclett.8b01723
|View full text |Cite
|
Sign up to set email alerts
|

Contact Line Pinning Is Not Required for Nanobubble Stability on Copolymer Brushes

Abstract: Whereas nanobubble stability on solid surfaces is thought to be based on local surface structure, in this work, we show that nanobubble stability on polymer brushes does not appear to require contact-line pinning. Glass surfaces were functionalized with copolymer brushes containing mixtures of hydrophobic and hydrophilic segments, exhibiting water contact angles ranging from 10 to 75°. On unmodified glass, dissolution and redeposition of nanobubbles resulted in reformation in mostly the same locations, consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Such nuclei may persist within the micro-/ nanoscale structures found on glass surfaces due to contact line pinning and may expand to form cavitation bubbles when mechanical shocks are imposed on the container. 26,27 Based on these observations, we hypothesize that a cavitationresistant surface should have low energy at the water interface, low roughness, and potentially a fluid-like structure to prevent stable contact line pinning. Hydrogels, three-dimensional hydrophilic polymeric networks, represent a material that possesses all of these attributes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such nuclei may persist within the micro-/ nanoscale structures found on glass surfaces due to contact line pinning and may expand to form cavitation bubbles when mechanical shocks are imposed on the container. 26,27 Based on these observations, we hypothesize that a cavitationresistant surface should have low energy at the water interface, low roughness, and potentially a fluid-like structure to prevent stable contact line pinning. Hydrogels, three-dimensional hydrophilic polymeric networks, represent a material that possesses all of these attributes.…”
Section: Introductionmentioning
confidence: 98%
“…Even when surfaces are treated to increase hydrophilicity, the surface roughness inherent to glass containers allows the heterogeneous nucleation of gas bubbles, which in turn facilitate cavitation and subsequently protein damage and aggregation. Such nuclei may persist within the micro-/nanoscale structures found on glass surfaces due to contact line pinning and may expand to form cavitation bubbles when mechanical shocks are imposed on the container. , …”
Section: Introductionmentioning
confidence: 99%
“…The fact that the surface nanobubble was able to move along on the substrate clearly demonstrated the stability of unpinned nanobubbles. Bull et al showed that the sites of nanobubble nucleation were randomly distributed on polymer brushes with hydrophobic and hydrophilic monomers, 4 indicating no preference for hydrophobicity. Using surface plasmon resonance microscopy, Wang et al 5 demonstrated that the migration of surface nanobubbles occurs after a series of stick−slip events.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this paper, we report a unique contrast agent that is designed to induce cavitation on the surface at low laser fluence and thus impart a nonlinear PA response while also maintaining a strong PA response in the linear regime. Previously, we showed that hydrophobically modified mesoporous silica nanoparticles facilitate acoustic cavitation by stabilizing the formation of gas pockets on the surface. Here, gold nanorods with plasmon resonance in the near infrared (NIR) were coated first with silica and then covalently modified with hydrophobic alkyl chains. To impart dispersibility in aqueous solvents, the nanoparticles were resuspended with a monolayer of phospholipids (Figure ).…”
Section: Introductionmentioning
confidence: 99%